2002
DOI: 10.1063/1.1476064
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of microindents in a nickel–titanium shape-memory alloy: A “self-healing” effect

Abstract: The thermally induced recovery of microscopic deformation in a nickel–titanium shape-memory alloy was examined. Surface deformation was simulated by indenting the alloy in the martensite phase at room temperature using both spherical and pyramidal indenters. We show that deformation in spherical microindents can be almost completely reversed by moderate heating. Partial recovery was observed for pyramidal impressions formed by a Vickers indenter and the recovery ratio was independent of the indentation depth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 16 publications
4
55
2
Order By: Relevance
“…This method of detecting size effects would also avoid errors in the estimation of hardness at small scales due to problems in determining contact area. In addition to hardness, the analysis of the load-displacement curves can help determine whether size effects exist in other types of deformation phenomena, as demonstrated in recent studies of the microscopic shape memory and superelastic effects in shape memory materials [272,273]. Thus, a paradigm shift may be called for in the study of indentation size effects from hardness measurements to the direct examination of the shape of indentation load-displacement curves with dimensional analysis as a guide.…”
Section: Discussionmentioning
confidence: 99%
“…This method of detecting size effects would also avoid errors in the estimation of hardness at small scales due to problems in determining contact area. In addition to hardness, the analysis of the load-displacement curves can help determine whether size effects exist in other types of deformation phenomena, as demonstrated in recent studies of the microscopic shape memory and superelastic effects in shape memory materials [272,273]. Thus, a paradigm shift may be called for in the study of indentation size effects from hardness measurements to the direct examination of the shape of indentation load-displacement curves with dimensional analysis as a guide.…”
Section: Discussionmentioning
confidence: 99%
“…3͒, even the material had experienced a large number of scratching cycles ͑e.g., 600͒. Ni et al 14 have observed such a self-healing effect due to M → A transformation by heating. Here, the selfhealing of the scratch track indicates that the groove was caused only by A → R → M phase transformation and that the wear rate under the spherical indenter was negligible at 22°C for the given load of 10 mN.…”
mentioning
confidence: 99%
“…Most experimental and modeling efforts on the NiTi shape memory alloys have focused primarily on the thermal-mechanical deformation characteristics and their micromechanisms [2][3][4][5][6][7][8][9]. Fatigue and fracture failure is one of important design considerations in many NiTi shape memory alloy products [1,10,11] but extensive experimental investigations are lacking [11].…”
Section: Introductionmentioning
confidence: 99%